Multispecies Politics in the City: Review of Tora Holmberg, Urban Animals: Crowding in Zoocities - Hunold, Christian (Humanimalia, 2019)
Tora Holmberg, Urban Animals: Crowding in Zoocities. Routledge Human–Animal Studies Series. New York: Routledge, 2015. 164 pp. $128.00 hc; $47.96 pb; $53.96 e-book.